2015
DOI: 10.1038/nbt.3124
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetics enables functional analysis of human embryonic stem cell–derived grafts in a Parkinson's disease model

Abstract: Recent studies have shown evidence of behavioral recovery after transplantation of human pluripotent stem cell (PSC)-derived neural cells in animal models of neurological disease1–4. However, little is known about the mechanisms underlying graft function. Here we use optogenetics to modulate in real time electrophysiological and neurochemical properties of mesencephalic dopaminergic (mesDA) neurons derived from human embryonic stem cells (hESCs). In mice that had recovered from lesion-induced Parkinsonian moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
228
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(237 citation statements)
references
References 48 publications
8
228
0
1
Order By: Relevance
“…In addition, they are capable of innervating distant target structures (Grealish et al, 2014) and modulating the glutamatergic input to striatal medium spiny neurons (Steinbeck et al, 2015). This has been made possible because of an improved understanding of mDA neuron development and a focus on studying human cells, overcoming species differences and allowing the preclinical development of stem cellbased cell replacement therapy for PD.…”
Section: Towards Cell Replacement Therapies For Pd With Pscsmentioning
confidence: 99%
“…In addition, they are capable of innervating distant target structures (Grealish et al, 2014) and modulating the glutamatergic input to striatal medium spiny neurons (Steinbeck et al, 2015). This has been made possible because of an improved understanding of mDA neuron development and a focus on studying human cells, overcoming species differences and allowing the preclinical development of stem cellbased cell replacement therapy for PD.…”
Section: Towards Cell Replacement Therapies For Pd With Pscsmentioning
confidence: 99%
“…Optogenetics thus allows for the noninvasive activation or inhibition of specific cells with light, a method that can be leveraged to combat a wide range of neurological conditions. Already, the potential of optogenetic techniques has been demonstrated in sciatic nerve injury [2], Parkinson's disease [3], epilepsy [4], depression [5,6], and retinal degeneration [7,8]. In this work, we describe a new method of using optogenetic techniques to study retinal circuit interactions between neurons and vascular cells, and show how this general approach can be potentially applied to treat neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To probe the mechanisms underlying the efficacy of this effect, Steinbeck et al optogenetically inhibited engrafted DA stem cells after motor recovery. They reported that inhibiting DA neurons resulted in the reappearance of motor deficits, indicating the essential role of DA neurons at the lesion site (Steinbeck et al, 2015).…”
Section: Parkinson's Diseasementioning
confidence: 99%